2019
DOI: 10.3390/geosciences9100415
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating GRACE Mass Change Time Series for the Antarctic and Greenland Ice Sheet—Methods and Results

Abstract: Satellite gravimetry data acquired by the Gravity Recovery and Climate Experiment (GRACE) allows to derive the temporal evolution in ice mass for both the Antarctic Ice Sheet (AIS) and the Greenland Ice Sheet (GIS). Various algorithms have been used in a wide range of studies to generate Gravimetric Mass Balance (GMB) products. Results from different studies may be affected by substantial differences in the processing, including the applied algorithm, the utilised background models and the time period under co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 48 publications
4
40
0
1
Order By: Relevance
“…It complements GRACE's inability to detect small glaciers. These results, based on the combined processing of the GRACE and SMB data, revealed that the GrIS total mass within the entire investigated period decreased at an annual rate of −267.77 ± 8.68 Gt/yr, and this accelerated by −12.12 ± 2.59 Gt/yr 2 , which is comparable with previous studies (e.g., the range −252 Gt/yr to −274 Gt/yr from Groh et al (2019) [48]; −255 Gt/yr from the Ice Sheet Mass Balance Inter-comparison Exercise (IMBIE) team (2019) [49]). During the same period, the Antarctic ice sheet's mass change rate was −162.91 ± 5.09 Gt/yr, with an acceleration of 10.12 ± 4.3 Gt/yr 2 .…”
Section: Discussion and Summarysupporting
confidence: 90%
“…It complements GRACE's inability to detect small glaciers. These results, based on the combined processing of the GRACE and SMB data, revealed that the GrIS total mass within the entire investigated period decreased at an annual rate of −267.77 ± 8.68 Gt/yr, and this accelerated by −12.12 ± 2.59 Gt/yr 2 , which is comparable with previous studies (e.g., the range −252 Gt/yr to −274 Gt/yr from Groh et al (2019) [48]; −255 Gt/yr from the Ice Sheet Mass Balance Inter-comparison Exercise (IMBIE) team (2019) [49]). During the same period, the Antarctic ice sheet's mass change rate was −162.91 ± 5.09 Gt/yr, with an acceleration of 10.12 ± 4.3 Gt/yr 2 .…”
Section: Discussion and Summarysupporting
confidence: 90%
“…The gravity field signal arising from each basin and Ellesmere Island is calculated in the spectral domain, filtered identical to the GRACE/GRACE-FO data, and then adjusted in scale for each basin to least-squares minimize the difference between the modelled and observed spatial gravity field signal over the GrIS and Ellesmere Island. Using alternate GrIS mass change times series available at http://gravis.gfz-potsdam.de/home, which is based on the inversion schemes of 59 , as well as using AV RL06 with the inversion approach of 28 , we estimate that different assumptions underlying the gravimetric inversion introduce an uncertainty of ±25 Gt for the monthly estimate. These values are consistent with the ±26 Gt uncertainty presented in Table A.1 of 27 and included in our GrIS time series.…”
Section: Grace/grace-fo Solution Combinationmentioning
confidence: 99%
“…To isolate LWS in GRACE mascon, we removed the glacier signals from the data over land based on Wouters 63 . The standard error is based on noise assessment by Groh 64 . Prior to the GRACE period, information on the LWS component comes from reanalysis products over 1993-2002: Modern Era Retrospective-analysis for…”
Section: Land Water Storage (Lws)mentioning
confidence: 99%